The Impact of Social Media Influencers Focused on Health on Marketing and Consumer Behavior on Instagram in Czech Republic - Ziegler, Dominik; Lhotáková, Markéta, 1971-; Halík, Jaroslav, 1961-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis explores the impact of health-focused social media influencers on consumer behavior and marketing strategies on Instagram in the Czech Republic. It provides an overview of the evolution of influencer marketing, highlighting the shift from traditional marketing methods to digital platforms and influencers. The research focuses on Instagram users interested in health and fitness content and uses a questionnaire survey to understand how these influencers affect consumer behavior, including engagement levels and purchasing decisions. The research explores various aspects of influencer marketing on Instagram, such as the authenticity of influencers and their content, how they use Instagram's features, and their overall credibility and impact on consumer decision-making. The study demonstrates that consumer trust in influencers varies significantly, with a noteworthy impact on their health and lifestyle choices. The ultimate goal of this analysis is to provide insights into effective digital marketing strategies and the real influence of health-focused influencers on Instagram. The research offers recommendations for marketers on how to leverage these insights in the Czech market. The data-driven approach ensures a comprehensive understanding of the current landscape of influencer marketing within a localized context, making a valuable contribution to both academic discourse and practical marketing strategies.
Vedoucí práce: Markéta Lhotáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses